Structural and functional characterization of a calcium-activated cation channel from Tsukamurella paurometabola - Balasundaresan Dhakshnamoorthy (Nature Portfolio, 2016)
Tetrameric cationic channels specificity is determined by the sequence and structural conformation of their selectivity filter. Here, the authors show that a cationic channel from Tsukamurella paurometabola is non-selective due to a Ca2+-binding motif within its unusual proline-rich filter.